ANALYSIS OF TEST ITEM ON THE FINAL TEST SEMESTER EXAM ON ARABIC SUBJECTS - Prihartini, Yogia; Buska, Wahyudi; Hasnah, Nur (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
This research is aimed; (a) to give a description about Arabic final semester test questions arrangements procedure at the Faculty of Tarbiyah and Teacher Training in UIN Imam Bonjol Padang. (b) to give a description about the quality of the test as seen from its validity, reliability, difficulty, and differentiation capacity. (c) to give a description that the lecturers never did an exam questions analysis of Arabic exam subject at Faculty of Tarbiyah and Teacher Training in UIN Imam Bonjol Padang. This research uses the descriptive method with quantitative and qualitative data. The population within this research is the college students of Tadris major in faculty of Tarbiyah and Teacher Training who follows the final semester exam of 2017-2018 tenet years, especially in Arabic test subject. The sample taken during this research is the college students from the Tadris major, who followed the final semester exam on Arabic subject, by using the purpose sampling technique. The data collecting technique used was documentation, interview, and questionnaires. The results of this research are (1) the types of this tests are achievement test from the teaching objectives aspect, teacher-made test from the arrangement aspect, summative test from the time of implementation aspect, written test from the method of performing aspects, and subjective test from the answer scoring aspect, (2) the quality of Arabic test year 2017/2018: (a) validity sufficient, (b) test reliability is high which is 0,74, (c) the difficulty is easy earning it a ‘bad’ category, which is 45 numbers of questions or 11,11%, (d) the differentiation capacity is bad, which is 45 numbers of questions, or 22,22%, (3) the reason why the lecturers and question maker team did not held a question analysis are as follows: (a) some of the Arabic lecturers in faculty of Tarbiyah and Teacher Training in UIN Imam Bonjol Padang are not scholars of Arabic education major or not lenient with S-1 and S-2 academic degree, (b) they have zero experience in doing test analysis, (c) there is no order from the authorities which motivates the lecturers in doing test analysis, (d) the lack of understanding about analysis, and (e) there are lecturers who have never received training or seminar about evaluation and analysis.